2003
DOI: 10.1124/mol.64.6.1295
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Central Nervous System Distribution and Pharmacology of the Mouse 5-Hydroxytryptamine-6 Receptor Compared with Rat and Human Receptors Investigated by Radioligand Binding, Site-Directed Mutagenesis, and Molecular Modeling

Abstract: There is increasing evidence for a role of 5-hydroxytryptamine-6 (5-HT 6 ) receptors in cognitive function. In the rat and human brain, 5-HT 6 receptors are widely expressed and highly enriched in the basal ganglia. However, in the mouse brain, only very low levels of 5-HT 6 receptor mRNA and receptor protein, measured by TaqMan reverse transcriptase-polymerase chain reaction and selective radioligand binding, could be detected, with no evidence of enrichment in the basal ganglia. The mouse receptor was cloned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
128
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(137 citation statements)
references
References 35 publications
8
128
0
1
Order By: Relevance
“…We attempted to confirm loss of protein product via autoradiography using the ligand 125 I-SB258585 (Roberts et al, 2002); however, we were unable to detect specific binding in wild-type brains. This finding is consistent with recent observations indicating that the affinities of ligands used to characterize 5-HT 6 Rs in the rat (such as 125 I-SB258585) demonstrate reduced affinity for the mouse homolog, and that 5-HT 6 R expression levels in the mouse are reduced relative to those in the rat (Hirst et al, 2003). Heterozygote crosses produced wild-type, heterozygous, and homozygous mutant mice in the expected Mendelian ratios, indicating that the mutation does not impair embryonic or postnatal viability.…”
Section: Generation Of 5-ht 6 R Null Mutant Micesupporting
confidence: 92%
See 1 more Smart Citation
“…We attempted to confirm loss of protein product via autoradiography using the ligand 125 I-SB258585 (Roberts et al, 2002); however, we were unable to detect specific binding in wild-type brains. This finding is consistent with recent observations indicating that the affinities of ligands used to characterize 5-HT 6 Rs in the rat (such as 125 I-SB258585) demonstrate reduced affinity for the mouse homolog, and that 5-HT 6 R expression levels in the mouse are reduced relative to those in the rat (Hirst et al, 2003). Heterozygote crosses produced wild-type, heterozygous, and homozygous mutant mice in the expected Mendelian ratios, indicating that the mutation does not impair embryonic or postnatal viability.…”
Section: Generation Of 5-ht 6 R Null Mutant Micesupporting
confidence: 92%
“…Additionally, species differences in 5-HT 6 R mRNA expression may contribute to species differences in behaviors sensitive to 5-HT 6 R function. Recent evidence indicates that differences between mouse and rat/human 5-HT 6 R receptor sequences are associated with differences in their affinities for 5-HT 6 R antagonist compounds, while not altering binding affinities for serotonin (Hirst et al, 2003).…”
Section: -Ht 6 R-influenced Behaviorsmentioning
confidence: 99%
“…In the latter study, however, there was no change of habitual feeding on a normal diet in 5-HT6 receptor knockout mice. The interpretation of these findings should be seen with some caution, as the central distribution of this receptor is different in mice compared to rats and humans [115]. Whereas 5-HT2C…”
mentioning
confidence: 91%
“…receptors are one of the most recently identified serotonin receptor subtypes (Monsma et al, 1993;Plassat et al, 1993;Ruat et al, 1993), and are coupled to a G stimulatory protein, inducing cAMP through adenylate cyclase stimulation (Monsma et al, 1993). Several in situ hybridization studies have shown robust mRNA expression in rat and human striatum, nucleus accumbens, cortex and olfactory tubercle, with moderate expression in the hippocampus and thalamus (Gerard et al, 1996;Ward and Dorsa, 1996), whereas expression in mouse brain is very low compared to rat or human brain (Hirst et al, 2003). Immunohistochemical localization of 5-HT 6 receptors has been detected in the above regions as well as the cerebellum and substantia nigra (Gerard et al, 1997;Hamon et al, 1999).…”
Section: Introductionmentioning
confidence: 96%